2016
DOI: 10.1186/s12879-016-1472-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends of reported foodborne diseases at the Ridge Hospital, Accra, Ghana: a retrospective review of routine data from 2009-2013

Abstract: BackgroundThere are over 250 foodborne diseases and are of growing public health concern worldwide. The distribution of these diseases varies from one locality to the other. Foodborne diseases come about as a result of ingestion of food contaminated with microorganisms or chemicals. The most common clinical presentation of foodborne disease takes the form of gastrointestinal symptoms; although other systems of the body can also be affected and represents a considerable burden of disability as well as mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…According to the [34], an average of 10,000-20,000 persons per 1,000,000 of the world's population suffer yearly from foodborne diseases from ingesting adulterated food items in developing countries. Even though Ghana is yet to have sentinel sites or any documented surveillance system for foodborne diseases [4], statistics from the [35] indicated that 420,000 cases of foodborne diseases are recorded in the outpatient departments of Ghana annually with death estimate of about 65,000 at a total cost of US$69 million to the Ghanaian economy. In arguing for the push factors behind the surge in foodborne diseases emanating from the ingestion of adulterated food items, [4] recount poor personal hygiene, poor sanitation, attitudes toward food hygiene and overcrowding.…”
Section: Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the [34], an average of 10,000-20,000 persons per 1,000,000 of the world's population suffer yearly from foodborne diseases from ingesting adulterated food items in developing countries. Even though Ghana is yet to have sentinel sites or any documented surveillance system for foodborne diseases [4], statistics from the [35] indicated that 420,000 cases of foodborne diseases are recorded in the outpatient departments of Ghana annually with death estimate of about 65,000 at a total cost of US$69 million to the Ghanaian economy. In arguing for the push factors behind the surge in foodborne diseases emanating from the ingestion of adulterated food items, [4] recount poor personal hygiene, poor sanitation, attitudes toward food hygiene and overcrowding.…”
Section: Researchersmentioning
confidence: 99%
“…The concern and attention given to food safety in Ghana and around the world arises due to the upward trend of foodborne illness incidence rates over the past 20 years both locally [3,4] and internationally [5,6]. Scallan et al,[7] paint a very frightening statistics from the United States of America when they reported that out of the 9.4 million incidences of foodborne illness caused by 31 major pathogens, there were 55, 961 hospitalizations and 1,351 deaths.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, Africa and Asia are perceived to have the highest incidence of foodborne disease. There are over 250 foodborne diseases [ 4 , 5 ]. A study in Ghana using data from 2009 to 2013 revealed cholera as the predominant foodborne disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Katanga reported that only 61% of those surveyed knew that cholera could be transmitted through food [28]. Of all food-borne illnesses reported at Ridge Hospital in Accra, Ghana, from 2009 to 2013, cholera comes out on top at 83.9% [35].…”
Section: Discussionmentioning
confidence: 99%